Malpositioned dialysis catheters: A case series - Desai , A.; Bennikal , M.; Bangari, G.; Janaky, M.; Manjunath , R. (Ukrainian Journal of Nephrology and Dialysis, 2022)
Hemodialysis catheters (HDC) are the commonly used vascular access for hemodialysis. Functioning access is essential for adequate dialysis. Dialysis catheter insertion under ultrasound guidance is now standard practice and has reduced the incidence of mechanical complications during catheter insertion. However, complications such as tip misplacement and puncture of the mediastinum cannot be prevented by ultrasound-guided procedures alone. We report four cases of abnormal positioning of HDC insertion and emphasize the importance of fluoroscopy or radiography after the procedure to verify the position of the catheter